Neural activity during production of rorschach responses: An fMRI study. (30th April 2017) - Giromini, Luciano; Viglione, Donald J.; Zennaro, Alessandro; Cauda, Franco
Abstract: Recently, a lot of effort has been made to ground Rorschach interpretations to their evidence base. To date, however, no studies have yet described, via fMRI, what brain areas get involved when one takes the Rorschach. To fill this gap in the literature, we administered the ten-inkblot stimuli to 26 healthy volunteers during fMRI. Analysis of BOLD signals revealed that, compared to fixating a cross, looking at the Rorschach inkblots while thinking of what they might be associated with higher temporo-occipital and fronto-parietal activations, and with greater activity in some small, sub-cortical regions included in the limbic system. These findings are in line with the traditional conceptualization of the test, as they suggest that taking the Rorschach involves (a) high-level visual processing, (b) top-down as well as bottom-up attentional processes, and (c) perception and processing of emotions and emotional memories. Highlights: We used fMRI to inspect what brain areas get involved when one takes the Rorschach. Participants (n =26) were instructed to look at each inkblot and think of what it might be. We compared BOLD signals associated with exposure to the Rorschach vs. fixation of a cross. A GLM with separate subject predictors and FDR adjustment (q =.05) was performed on the entire sample. The Rorschach condition activated brain areas typical of visual processing, top-down and bottom-up attentional networks, and perception and processing of emotions.